A MECHANISM FOR DEVELOPING THE TECHNICAL COMPETENCE OF FUTURE AGRICULTURAL TEACHERS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the formation of technical competence in future teachers in the field of agriculture and its content, the role and importance of basic competencies in their preparation for professional activities, the formation of knowledge, skills and abilities among students in general and special subjects. through interdisciplinary communication, pedagogical and technical issues, such issues as the mechanism for the development of technical competence of students based on knowledge and an integrative-differential approach to it is explained.